PENERAPAN JURNALISME SASTRAWI DALAM BUKU HIROSHIMA KARYA JOHN HERSEY - Fifiyanti Abdurahman; Feri Sanjaya; Faisyal - (FISIP Universitas Bung Karno, 2021)
Abstract The Hiroshima by John Hersey is a book that tells the story of a event when the atomic bomb was dropped on the Japanese city of Hiroshima on August 6, 1945. One year later, John Hersey observed and dug up information for three weeks, then interviewe more than 40 people. eventually, he chose six victims that have interesting story where survived from atomic bomb. They are Miss Toshiko Sasaki, Doctor Masazaku Fuji, Mrs Hatsuyo Nakamura, Father Wilhelm Kleinsorge, Doctor Terfumi Sasaki, and Pastor Kiyoshi Tanimoto. This research uses qualitative approach. With descriptive qualitative method. The unit of analysis that used in this study is the book Hiroshima by John Hersey with observing excerpts of the story in the book. As well as researching whether the book belongs to the category of literary genre journalism or not. The collected data is then analyzed using journalism theory literary works according to Robert Vare, who said that in writing journalism, In literature there are seven considerations that must be considered. These include facts, conflicts, character, access, emotion, time travel and novelty elements. The results of this study shows that the book Hiroshima is a work of literary journalism and has fulfilled the seven elements.Keywords: Literary Journalism, Hiroshima, Literature ABSTRAK Buku Hiroshima karya John Hersey merupakan buku yang mengisahkan kejadian nyata ketika bom atom dijatuhkan di kota Hiroshima Jepang pada 6 Agustus 1945. John Hersey melakukan peliputan di kota tersebut setelah satu tahun kemudian. Ia meliput selama tiga minggu dan mewawancarai 40 orang lebih, kemudian mengangkat kisah enam korban yang memiliki perjalanan menarik ketika bertahan hidup paska bom dijatuhkan. Mereka adalah Nona Toshiko Sasaki, Dokter Masazaku Fuji, Nyonya Hatsuyo Nakamura, Pastur Wilhelm Kleinsorge, Dokter Terfumi Sasaki, dan Pendeta Kiyoshi Tanimoto. Penelitian ini menggunakan pendekatan kualitatif. Dengan metode kualitatif deskriptif. Unit analisis yang digunakan dalam penelitian ini adalah buku Hiroshima karya John Hersey dengan mengobservasi cuplikan kisah di buku tersebut. Serta meneliti apakah buku itu termasuk kategori jurnalisme bergendre sastra atau tidak. Data yang terkumpul kemudian di analisis dengan menggunakan teori jurnalisme sastrawi menurut Robert Vare, yang mengatakan dalam menulis karya jurnalisme sastra ada tujuh pertimbangan yang harus diperhatikan. Diantaranya fakta, konflik, karakter, akses, emosi, perjalanan waktu dan unsur kebaruan. Hasil penelitian ini menunjukkan bahwa buku Hiroshima merupakan karya jurnalisme sastrawi dan telah memenuhi ketujuh unsur tersebut. Kata kunci : Jurnalisme Sastrawi, Hiroshima, Sastra